3D reconstruction of peripheral nerves from optical projection tomography images: A method for studying fascicular interconnections and intraneural plexuses - Prats-Galino, Alberto; Čapek, Martin; Reina, Miguel A; Cvetko, Erika; Radochova, Barbora; Tubbs, R Shane; Damjanovska, Marija; Stopar Pintarič, Tatjana (Clinical anatomy (New York, N.Y.), 2018)
The general microscopic characteristics of nerves are described in several textbooks of histology, but the specific microanatomies of most nerves that can be blocked by anesthesiologists are usually less well known. Our objective was to evaluate the 3D reconstruction of nerve fascicles from optical projection tomography images (OPT) and the ability to undertake an internal navigation exploring the morphology in detail, more specifically the fascicular interconnections. Median and lingual nerve samples were obtained from five euthanized piglets. OPT images of the samples were acquired and 3D reconstruction was performed. The OPT technique revealed the inner structure of the nerves at high resolution, including large and small fascicles, perineurium, interfascicular tissue, and epineurium. The fascicles were loosely packed inside the median nerve and more densely so in the lingual nerve. Analysis of the 3D models demonstrated that the nerve fascicles can show six general spatial patterns. Fascicular interconnections were clearly identified. The 3D reconstruction of nerve fascicles from OPT images opens a new path for research into the microstructure of the inner contents of fascicular nerve groups and their spatial disposition within the nerve including their interconnections. These techniques enable 3D images of partial areas of nerves to be produced and could became an excellent tool for obtaining data concerning the 3D microanatomy of nerves, essential for better interpretation of ultrasound images in clinical practice and thus avoiding possible neurological complications. Clin. Anat. 31:424-431, 2018. © 2017 Wiley Periodicals, Inc.
Keywords: peripheral nerve; Tomography, Optical; lidé; Peripheral Nerves; zobrazování trojrozměrné; 3D reconstructions; periferní nervy; Imaging, Three-Dimensional; fascicles; optická tomografie; optical projection tomography; Humans